The littlest tree - Tazewell, Charles (Ideals Children's Books, 1997)
Solomon and everyone else in the Celestial City are surprised when a paltry sprig which has been lovingly decorated by a group of orphans in a war-torn city is chosen to be the Son's Birthday Tree.